Contributions of Frantz Fanon to the construction of another method in and from Latin America and the Caribbean - Laura Celina Vacca; María Mercedes Palumbo (Perspectivas Metodológicas​)
This article inquiries about the methodological principles in the major works of Frantz Fanon in which we identify a contribution to establish “another” method in the frame of an “new” anti-colonial and antiracist science. As a starting point, we consider the importance of this contribution to the construction of a way of doing science in Latin America and the Caribbean that question the positivist tradition.  From a hermeneutic and interpretive methodology, we tackle four dimensions of analysis that outline the methodological proposal of the author: the subject-subject relation, the situationality of thought, the heterogeneity of knowledges involved, and the interweaving between science and politics